KAJIAN PENGENDALIAN PENYAKIT LAYU Fusarium oxysporum DENGAN Trichoderma sp. PADA TANAMAN CABAI - Heriyanto , Heriyanto (Jurnal Ilmu-Ilmu Pertanian, 2019)
The study aims to determine the concentration of Trichoderma sp. effective for controlling Fusarium oxysporum wilt in chilli plants, which was carried out in Banguntapan Village, Banguntapan District, Bantul District, from March to October 2018. The study used a complete randomized block design consisting of 5 treatments of Trichoderma sp. ie 0.0 g, 2.50 g, 5.0 g, 7.50 g and 10.0 g biomass / m2 with 4 replications each treatment. Application was carried out by isolating the biomass of Trichoderma sp. inoculated in 2.5 kg of organic fertilizer / compost, then sprinkled on the ield before chilli seedlings were planted. Based on the analysis of the incubation period and the intensity of the attacks, showed that the treatment of Trichoderma sp. with a concentration of 10.0 g of biomass gave effective results and reduced the intensity of Fusarium oxysporum wilt attack by 12.15 percent.